Axiological and Methodological Analysis of Folk Games - Teplova A.B.; Chernushevich V.A. (Психолого-педагогические исследования)
Play is defined as a special form of free activity according to the rules, that, unlike work, does not produce an alienable product. The socio-psychological mechanism of the influence of the conditions of the game on the participants is considered. Conceptual analysis of the game from the point of view of the key, meaning-forming experience in the game – happiness-joy, shows that this experience is due to the peculiarities of the relations of the participants: internal self-restraint (conscience) and conflict-free communication (the presence of sympathy, empathy, sympathy, assistance). These factors explain the corrective and preventive resources of play practice in the work of specialists with deviant behavior in children and adolescents (irresponsibility, aggression, violation of social norms...). Game practice simulates favorable social conditions for development. The semantic definition of the experience of happiness-joy is made based on a meaningful understanding of children's happiness by specialists in working with children as their professional target setting. The phases of the formation of the game are defined and shown using examples of folk games: formal adoption of the rules, individual self-realization within the framework of the rules, individual self-realization within the framework of the rules and the value of the gaming community.